Clinical utility of 18F-fluorodeoxyglucose positron emission tomography/computed tomography in Takayasu arteritis -- a report of 3 demonstrative cases. (2013)
Takayasu arteritis (TA) is a granulomatous disease affecting aorta and its main branches1. 18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) may be useful in assessing disease activity of TA. We describe 3 demonstrative cases. In case 1, a 44-year-old man was admitted with a fever of unknown origin. The levels of acute phase reactants (APR) were elevated. Pulse in the left upper arm was undetectable and the …